Partial differential equations : An introduction - Young, Eutiquio C (Allyn and Bacon, 1972)
This book is the outgrowth of an introductory course in partial differential equations wich the author has given for a number of years. The students are mostly undergraduates who ar majors of mathematics, engineering, or the physical sciences. The book treats principally linear partial differential equations of the first and second order involving two independent variables. Problems involving second-order differntial equations are discussed with reference to the three prominent classical equation, and Laplace's equations. These equations serve as prototypes for the three main types of linear partial differential equations of second order. The kinds of problems that are treated for each of these equations in two variables as well as the properties of the solutions are generally tipical of what can be expected with more general differential equations of the same type in three of more independent variables.